Kinetics of xylan autohydrolysis during subcritical hydrothermal pretreatment of oil palm frond pressed fiber - Mohd Yusof, Siti Jamilah Hanim; Roslan, Ahmad Muhaimin; Zakaria, Mohd Rafein; Hassan, Mohd Ali; Shirai, Yoshihito (Springer, 2021)
A kinetic study was performed to determine the kinetics of hemicellulose (xylan) hydrolysis during subcritical hydrothermal pretreatment of OPFPF. The trend of xylan conversion was observed over 40-min treatment time at two different conditions: without CO2 addition at four different temperatures (170, 180, 190, and 200 °C), and with CO2 addition of 0.5 and 1 MPa at 180 °C. Experimental data obtained was subsequently fitted into the selected first-order kinetic model. It was demonstrated that the experimental data was comparable to the predicted values, indicating the suitability of the chosen model for quantitative interpretation of the experimental results. In addition, the reaction rate was found to improve with the rise of temperature and the presence of CO2, as indicated by the increasing values of reaction rate constants, k. The relationship between k and temperature was successfully established through Arrhenius equation, where the activation energies for xylan conversion were found in the range of 43.49 to 170.16 kJ/mol. Based on the results, subcritical pretreatment of OPFPF at 180 °C and 0.5 MPa CO2 was suggested suitable for high glucose recovery from OPFPF due to high xylan removal rate and low generation of hydrolysis byproduct which is beneficial for successful saccharification and fermentation. This study provides knowledge in the kinetics of xylan autohydrolysis in oil palm frond, and hence could contribute in the process design for recovery of glucose and hemicellulose derivatives such as XOS and furfural from oil palm residues.